Double Solitaire Mechanical Thrombectomy in Acute Stroke: Effective Rescue Strategy for Refractory Artery Occlusions? - Klisch, J.; Sychra, V.; Strasilla, C.; Taschner, C.A.; Reinhard, M.; Urbach, H.; Meckel, S. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Mechanical thrombectomy by using a single stent retriever system has demonstrated high efficacy for recanalization of large-artery occlusions in acute stroke. We aimed to evaluate the feasibility, safety, and efficacy of a novel double Solitaire stent retriever technique as an escalating treatment for occlusions that are refractory to first-line single stent retriever mechanical thrombectomy. MATERIALS AND METHODS: All patients treated with the double stent retriever technique by using the Solitaire system were retrospectively selected from 2 large neurointerventional centers. Time to recanalization, angiographic (TICI) and clinical outcomes (mRS), and complications were assessed. RESULTS: Ten patients (median NIHSS score, 16; mean age, 70 years) with MCA M1 segment (n = 5) and terminal ICA (n = 5 including 2 ICA tandem) occlusions were included. Prior single stent retriever mechanical thrombectomy had been performed in 9 patients (median number of passes, 3). Median time to recanalization was 60 minutes (interquartile range, 45–87 minutes). Procedure-related complications occurred in 1 patient; overall mortality was 20%. Recanalization of the target vessel (TICI 2b/3) was achieved in 80%. Good clinical outcome (mRS 0–2) was 50%. CONCLUSIONS: In this preliminary feasibility study, the double Solitaire stent retriever technique proved to be an effective method for recanalization of anterior circulation large-artery occlusions refractory to standard stent retriever mechanical thrombectomy. DACdistal-access catheterICATinternal carotid artery terminusMTmechanical thrombectomySRstent retriever